The Emerging WDM EPON - Radivojević, Mirjana; Matavulj, Petar; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book proposes dynamic wavelength and bandwidth allocation (DWBA), a hybrid of time-division multiplexing (TDM) and wavelength-division multiplexing (WDM), which offers a solution for service providers faced with multiservice networks. It discusses different models, architectures and implementations and evaluates their performance.
Introduction -- Quality of service implementation -- PON evolution -- Single-channel EPON -- Multichannel EPON -- WDM EPON architecture -- Performance evaluation.
Keywords: Telecommunication; Computer networks .; Application software; Communications Engineering, Networks; Computer Communication Networks; Computer and Information Systems Applications